COMPARATIVE ANALYSIS OF CUSTOMER ENGAGEMENT ON BRANDED FASHION APPAREL IN MANADO - Arsyad, Annisa M.T; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: For centuries, textiles and clothing styles have been one of the most obvious and poignant indicators of cross-cultural interchange. With the rapid rise of globalization over the past several decades, the spread of fashion across global cultures has mirrored the changes in economy, culture, and daily life that globalization has brought. This research aims to see if there any significant difference of Customer Engagement between Single Woman and Married Woman branded fashion apparel in Manado. This research is using quantitative research methodology. The populations in this research are all woman who buy branded fashion apparel in Manado. The sample for this research is consists of 100 people, divided into 50 Single Woman and 50 Married Woman. The result shows that there is a significant difference in terms of consumer engagement between single woman and married woman on branded fashion apparel in terms of consumer engagement. The mean value of the married woman is higher than the single woman. The recommendation of this research is hence the focus of the improvement in order to develop a better strategy approach to boost the sales to the brand should be prioritized mostly in these 3 indicators which are trust, brand community, and loyalty, particularly aimed to the single woman.Keywords: customer engagement, engagement marketing.